Effects of Land Use Changes On Flora Diversity in Oba Division of the Cross River National Park, Nigeria (2015)
The Oban Division of the Cross River national Park, Nigeria, is a globally renowned biodiversity hotspot. The area is experiencing rapid land use changes and little efforts have been made to document the effects of the changes on biodiversity. The study investigated the effects of different land use types on flora composition, distribution and diversity in the area with a view to generating data that will support conservation decisions. The area was stratified into four: primary forest (core), secondary forest (buffer), farm fallow and plantation. Ten transects of 2 km length each were systematically located in each land use type. Four sample plots of 50×50 m were located on each transect at an interval of 500 m. Each plot was subdivided into 10×10 m subplots; and nine subplots were randomly selected for the enumeration of trees, shrubs and climbers. A 1×1 m miniplot was then located at the centre of each subplot for herb enumeration. Flora species composition was estimated across the land use types using species diversity indices and Jaccard similarity indices. Composition, species richness and diversity of trees, shrubs and climbers all decreased from the core to plantation. However, herb species composition, richness and diversity increased from core to farm fallow. Significant differences in species composition were obtained across land use types at 5%. The highest tree species similarities were recorded between core and buffer. The highest similarities for shrubs, herbs and climbers were recorded between farm fallow and plantation. The absence of species previously recorded in the core, and in the other land use types makes it imperative that conservation efforts be improved and extended to areas beyond the core in order to save the remaining flora diversity in this forest